Continuing Professional Development (CPD) melalui Webinar dan Kompetensi Perawat - Yuliana Bernadetta; Rr. Tutik Sri Hariyati; Hening Pujasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify the competence of nurses after participating in CPD and the process of implementing CPD. The research method uses a quantitative descriptive method with a cross-sectional approach. The analysis results show a significant relationship between Continuing Professionalism Development (CPD) through webinars and nurse competence (p = 0.000). This study found that from the nurse's characteristics, only the level of education influenced the activities to take part in CPD through the webinar, a value of p < 0.05. In contrast, the other nurses' characteristics had no effect. In conclusion, nurse characteristics and CPD implementation activities affect the competencies obtained only by 46.4%, and factors outside of nurse characteristics influence the rest. Keywords: CPD, Nurse Competency, Webinar